(untitled) (Bangladesh Journal of Plant Taxonomy, 2024)
The Purbachal Sal Forest, a vital ecosystem in the outskirts of Dhaka city facing biodiversity decline, was assessed for its plant composition and public perception of its management and conservation. A total of 190 species under 61 families have been recorded from the study area following the random quadrat method. Analyses showed that among the 190 species, the most abundant tree and shrub in the forest are Shorea robusta Roxb. ex Gaertn. and Melastoma malabathricum L., respectively. In case of dominance based on the Importance Value Index, Shorea robusta is the most dominant tree, followed by Melastoma malabathricum as the most dominant shrub. The percentages of native and exotic species were found to be 75% and 25%, respectively. The Shannon-Wiener Diversity Index in the study area was 0.61, whereas Simpson’s and Margalef’s Indices were 0.178 and 4.77, respectively. From interviews with visitors and stakeholders, this study revealed that the majority of them responded negatively about the presence of exotic species in the forest, and on the other hand, they responded positively on the question of incorporating experts in the management plan of the forest. A number of threats to the species diversity of the forest were recorded through observation in the field and stakeholders’ interviews, such as invasive alien species (IAS) intrusion, habitat destruction, agricultural practice, and deforestation. A set of recommendations, including planting more wildlife-supporting native species, preventing the spread of IAS like Parthenium L. and incorporating experts in the forest’s management, was developed for present and future management of Purbachal Sal Forest. Bangladesh J. Plant Taxon. 31(2): 279-292, 2024 (December)